COMPARISON OF GROWTH AND YIELD OF SOYBEAN (Glycine max L) WITH VARIATION OF BIOFERTILIZER DOSAGE IN THE RAINY SEASON - Adi Oksifa Rahma; Ida Marina (Fakultas Sains Terapan Universitas Suryakancana, 2023)
The purpose of this research was to evaluate the influence of soybean cultivar combinations and biofertilizer dosages on the growth and yield of soybean plants during the rainy season. The analysis results indicated that these combinations did not have a significant effect on the growth and yield of the plants. The variations among treatments were predominantly influenced by the choice of cultivar. The use of biofertilizers enhanced nutrient availability for the plants but did not consistently yield significant results. Rainy season and other environmental factors also affected plant growth. Cultivar variations and genetic factors played a role in yield variations as well. The use of biofertilizers provided benefits for soil structure and microbial activity. In terms of pod and seed quantities, the Deja 2 cultivar with biofertilizer dosages of 0 g/kg and 10 g/kg demonstrated the highest yields. There were no significant differences in root dry weight across all treatments, while the highest shoot dry weight was observed in the Grobogan cultivar with a biofertilizer dosage of 0 g/kg. In terms of weight per 100 seeds, the Grobogan cultivar with biofertilizer dosages of 0 g/kg, 5 g/kg, 10 g/kg, and 15 g/kg exhibited the highest weights. This research indicates that genetic factors, environment, and biofertilizer dosages play a role in the growth and yield of soybean plants. In terms of the number of soybean plant branches, some treatments showed the best results, but the impact of biofertilizer dosages was not significantly observed. Regarding root dry weight, there were no significant differences among the treatments, possibly due to suboptimal translocation of photosynthetic products to the roots resulting from high rainfall. However, shoot dry weight tended to increase in treatments with high rainfall conditions. The parameters of pod fill count and seed count per plant were also influenced by the combination of cultivars and biofertilizer dosages. Some treatments exhibited higher yields, particularly in the combination of the Deja 2 cultivar with a biofertilizer dosage of 0 g/kg.Â Â